Modelling of a hydrogen thermally driven compressor based on cyclic adsorption-desorption on activated carbon. (21st June 2019) - Sdanghi, G.; Nicolas, V.; Mozet, K.; Maranzana, G.; Celzard, A.; Fierro, V.
Abstract: Thermally driven hydrogen compression by cyclic hydrogen adsorption-desorption on activated carbon is presented therein. Hydrogen compression occurs through heat exchange, which allows physisorbed hydrogen to desorb at higher temperature in a given volume. The physical nature of hydrogen adsorption on porous carbon allows reversible desorption, and a flow of compressed hydrogen is then obtained by running adsorption/desorption cycles repeatedly. We investigated the feasibility of such a system through numerical simulations by taking into account both mass and energy balances, and adsorption thermodynamics. We showed that high-pressure hydrogen, up to 70 MPa, can be obtained by simply lowering and/or increasing the system temperature. Such a system opens new perspectives in the frame of the Hydrogen Supply Chain. Highlights: Cyclic adsorption-desorption allows obtaining high-pressure hydrogen. Our model successfully fitted formerly published experimental data. The evolution of hydrogen density with adsorption was calculated. The predicted adsorbed hydrogen density was 66 kg m −3 at 77 K and 4 MPa. 66 kg m −3 was somewhat lower than the liquid hydrogen density, 70.8 kg m −3 .